(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s world, classification algorithm is successfully applied to predict the zone based on the zip code of the dataset. Different classification algorithms can are applied to the dataset to devise method, which predicts the status of the zone for the given zip code available in the dataset. The accuracy of the methods differs from the classification algorithm used. It is very challenging to identify the best classification algorithm. Here, we attempt to make a comparative analysis and evaluations of the performance of different classification are done for the given data sets. As the datasets are getting increases, the algorithm performed better for its accuracy